2014
DOI: 10.1037/xap0000021
|View full text |Cite
|
Sign up to set email alerts
|

Using a general problem-solving strategy to promote transfer.

Abstract: Cognitive load theory was used to hypothesize that a general problem-solving strategy based on a make-as-many-moves-as-possible heuristic could facilitate problem solutions for transfer problems. In four experiments, school students were required to learn about a topic through practice with a general problem-solving strategy, through a conventional problem solving strategy or by studying worked examples. In Experiments 1 and 2 using junior high school students learning geometry, low knowledge students in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Other factors such as clinical placements and strategies used to enforce learning (McVicar et al, 2014), the time period evaluated (Craft et al, 2013;Kardong-Edgren et al, 2015;McVicar et al, 2015), the number of organ systems and type of organ system studied (Aari et al, 2004;Díaz-Mancha et al, 2016;Emke et al, 2016;Craft et al, 2017), and student factors such as age, gender, employment status, admission qualifications, personality, anxiety, self-efficacy, and support-seeking behaviors (Pitt et al, 2012). Thirdly, these studies described knowledge transfer from high school science to the first-year of the biosciences in university (Whyte et al, 2011;Youssef-Shalala et al, 2014;McVicar et al, 2015) or from theory to clinical (Booth et al, 2017;Günay and Kılınç, 2018;Alt-Gehrman, 2019) or practical (Wagner, 2014;Taylor et al, 2015;Emke et al, 2016;Culyer et al, 2018). However, none of these studies discussed organ-specific knowledge acquisition, transfer, and/ or its application in subsequent years of nursing education.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as clinical placements and strategies used to enforce learning (McVicar et al, 2014), the time period evaluated (Craft et al, 2013;Kardong-Edgren et al, 2015;McVicar et al, 2015), the number of organ systems and type of organ system studied (Aari et al, 2004;Díaz-Mancha et al, 2016;Emke et al, 2016;Craft et al, 2017), and student factors such as age, gender, employment status, admission qualifications, personality, anxiety, self-efficacy, and support-seeking behaviors (Pitt et al, 2012). Thirdly, these studies described knowledge transfer from high school science to the first-year of the biosciences in university (Whyte et al, 2011;Youssef-Shalala et al, 2014;McVicar et al, 2015) or from theory to clinical (Booth et al, 2017;Günay and Kılınç, 2018;Alt-Gehrman, 2019) or practical (Wagner, 2014;Taylor et al, 2015;Emke et al, 2016;Culyer et al, 2018). However, none of these studies discussed organ-specific knowledge acquisition, transfer, and/ or its application in subsequent years of nursing education.…”
Section: Introductionmentioning
confidence: 99%
“…The value of x in this case is referred to as the specified goal. According to Ayres & Sweller (1990), in solving such problems students often use a general problem-solver such as means-ends analysis and work backwards from the goal (see also Youssef-Shalala, Ayres, Schubert, & Sweller, 2014). For many students this creates a high cognitive load and reduces learning.…”
Section: Introductionmentioning
confidence: 99%
“…Simply pointing out to students that they should use a generic, cognitive skill may be beneficial when learning domain-specific content. Recently, Amina Youssef-Shalala, a PhD student of Paul Ayres and mine, Carina Schubert, a visitor from Germany, and I found that telling students that in the absence of domain-specific knowledge indicating how certain problems can be solved, they should use a strategy of randomly generating moves (YoussefShalala, Ayres, Schubert, & Sweller, 2014). For this strategy, students are told to make as many moves as they can without any reference to the goal of the problem.…”
Section: Instructional Consequences Of Evolutionary Educational Psychmentioning
confidence: 99%